2008
DOI: 10.1016/j.ijgo.2007.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cryotherapy treatment for cervical intraepithelial neoplasia

Abstract: Cryotherapy is an effective treatment for cervical precancerous lesions; it can easily be administered by general practitioners in primary care settings following visual inspection screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 14 publications
0
38
0
8
Order By: Relevance
“…24 In this study, the therapy was provided by general physicians, but midwives or other midlevel providers have performed the procedure in other settings with similar results. For example, in Dindigul district in India, Sankaranarayanan et al 25 found an overall cure rate of 81% among women with CIN 1 and 71% among women with CIN 2-3 when cryotherapy was provided by nurses in field clinics.…”
Section: Alternative Cervical Cancer Screening Approaches In Low-resomentioning
confidence: 94%
“…24 In this study, the therapy was provided by general physicians, but midwives or other midlevel providers have performed the procedure in other settings with similar results. For example, in Dindigul district in India, Sankaranarayanan et al 25 found an overall cure rate of 81% among women with CIN 1 and 71% among women with CIN 2-3 when cryotherapy was provided by nurses in field clinics.…”
Section: Alternative Cervical Cancer Screening Approaches In Low-resomentioning
confidence: 94%
“…This inexpensive and technically simple technique destroys abnormal tissue by freezing it with a probe cooled by liquid carbon dioxide (CO 2 ). A systematic review of 32 studies found that the procedure is safe and has an overall cure rate of almost 90% (Castro et al, 2003), and more recent studies have confirmed its effectiveness Luciani et al, 2008;Chamot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…5 Demonstration projects and randomized controlled screening trials have found that the effectiveness and efficiency of a single visit screen-and-treat strategy using VIA testing followed by treatment with cryotherapy are high. [6][7][8] VIA has sensitivity equal to or greater than the Pap test in detecting high-grade dysplasia, requires simple equipment, and provides immediate results. Cryotherapy is also more appropriate for low resource settings, as it does not rely on electricity and is inexpensive.…”
Section: Introductionmentioning
confidence: 99%